Upaya Pendidik PAI Dalam Meningkatkan Prestasi Belajar Siswa Kelas II di Sanggar Bimbingan Belajar Muhammadiyah Kampung Bharu Malaysia 2023 - Dewi Auriyanti Rangkuti; Mandra Saragih; Suci Perwita Sari; Ismail Saleh Nasution (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This study aims to find out the efforts of PAI educators in improving learning achievement, students also know whether the efforts made by PAI educators can increase student learning achievement. Muse metode qualitative research. This method is carried out to describe whether PAI learning achievement will increase with the efforts of the PAI educator. Among the efforts of PAI educators in improving student learning achievement are using methods that are adapted to the learning material, interestingly and fun, providing stories of prophets and friends, providing exercises, counseling guijugace / more precisely deepening the material, providing questions that can stimulate student activity, providing guijugace counseling / more precisely deepening the material, providing questions that can stimulate student activity, providing guijugace rahan, repeating the material for low grades at the same time different places, giving homework at the end of each material, doing daily replays once every 1 month. The efforts made by PAI educators in grade 2 at SB Muhamadiyah Kampung Bharu have good results, their learning achievement has increased even though it is a fairly long process also with not too rapid graphics. Keywords: Teacher Effort PAI, Student Achievement